Upaya Jepang dalam Melindungi Tenaga Kerja Asing Pada Technical Intern Training Program - Fauzan, Muchammad Rizki; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
This study aims to find out how Japan's efforts to protect foreign workers from exploitation and human rights violations in the Technical Intern Training Program (TITP) employ foreign nationals according to the International Labor Organization convention due to a shortage of labor (hitodebusoku). Even though Japan has ratified the International Labor Organization (ILO) convention and does not allow exploitation through several laws, Japan has been criticized for the exploitation and human rights violations against foreign workers such as underpayment of wages, illegal overtime, forced repatriation to the country. origin, hazardous and unsanitary working conditions. This research was conducted using descriptive qualitative method through literature study based on Mitchell's compliance theory. The results of this study indicate that Japan has ratified the ILO and in writing supports anti-exploitation efforts through the Labor Standards Act no. 49 of 1947 concerning Wages reinforced the Minimum Wages Law no. 137 of 1959 and the Industrial Safety and Health Act no. 57 of 1972, Labor Standards Inspector 1997, providing protection for trainees through JITCO and transferring trainee skills through On Job Training (OJT) as well as priority efforts in the promotion, strengthening and implementation of ratified ILO regulations. The results of this study indicate the need for the Japanese government to tighten the rules and supervision of TITP by companies in order to reduce cases of exploitation and human rights violations against foreign workers due to company non-compliance.